Factors influencing the satisfaction of International Students in Universiti Utara Malaysia towards Mobile Operators - Yusuf, Ismail Ali (2018)
The number of international students studying in Malaysian institution of higher education is constantly growing. The vast number of international students in Malaysia has supported not only to the country's education sector, but the telecommunication industry as well. Since, telecommunication market in Malaysia has been privatized, it has resulted in intense competition among market players and mobile service operators concern to retain their customer and attract new ones. Therefore, satisfying customer has been recognized as the best way to win the competition. Additionally, studies on international student satisfaction are still limited in number, although the issue is seen as important. The purpose of this study is to examine the relationship between service quality, perceived value, and brand awareness towards customer satisfaction in mobile service operators in Malaysia. The respondent of this study is the international students in UUM. A total of 340 questionnaires were distributed to international students in UUM, Sintok. Only 261 were useable for analysis. The data was analyzed using SPSS 25 to achieve the objectives of the study. The finding of this study has revealed that service quality and perceived value have significantly positive relationship with customer satisfaction. However, the brand awareness has negative relationship with customer satisfaction. Furthermore, the research framework of this study will contribute the literature in the context of customer satisfaction. It will also help mobile service managers to have further understanding on the influence of service quality and perceived value towards customer satisfaction. Finally, some limitations have paved the direction for future research.